Oblique magnetic fields and the role of frame dragging. Issue 1 (28th March 2019) - Karas, V.; Kopáček, O.; Kunneriath, D.; Tahamtan, T.
Abstract : Magnetic null points can develop near the ergosphere boundary of a rotating black hole through the combined effects of strong gravitational field and the frame‐dragging mechanism. The electric component does not vanish in the magnetic null, and an efficient process or particle acceleration can occur. The situation is relevant to starving (low‐accretion‐rate, such as the Milky Way's supermassive black hole [SMBH]) nuclei of some galaxies that exhibit only episodic accretion events. The presence of the magnetic field of external origin is an important aspect. We propose that such conditions can develop when a magnetized neutron star approaches the SMBH during late stages of its inspiral motion. The field lines of the neutron star dipole thread the black hole's event horizon and rapidly change their connectivity. We compare the case of a dipole‐type magnetic field of a sinking and orbiting star near a nonrotating black hole and the near‐horizon structure of an asymptotically uniform magnetic field of a distant source near a fast‐rotating black hole. Although the two cases are qualitatively different from each other, they both develop magnetically neutral null points near the event horizon.